Obecny stan techniki produkcji celulozy - zagadniene gospodarki wodno-ściekowej przemysłu celulozowniczego - Graczyk, Magdalena (Zielona Góra: Uniwersytet Zielonogórski)
The sulphite and sulphate pulp production is discussed as well as the characteristic ot chemical pulp factory wastes and their purification methods. Some up-to-date methods ot cellulose production with full wastewater recycling are also presented.
Keywords: celuloza; gospodarka wodno-ściekowa